State of the art on the main intervention methodologies in the field of emergency psychology: a systematic review - Romanelli, Michele; Taddeo, Flavia; Turchi, Gian Piero; Iudici, Antonio (Frontiers in Psychology, 2025)
In recent years, emergency psychology has emerged as an interdisciplinary discipline that integrates clinical, community and intercultural approaches to managing the psychological impact of critical events. However, the rapid evolution of the field has generated methodological fragmentation, hindering the definition of a unified disciplinary identity. While international guidelines (IASC and OMS) promote an integrated approach, other models focus on PTSD prevention and practitioner training. This review analyses the main types of interventions in the literature through a systematic analysis and thematic clustering of 27 articles. The results highlight a wide range of approaches, from methodologies for the development of coping skills and social adaptation, to psychological support strategies, to clinical-diagnostic models borrowed from emergency medicine. However, the risk of reducing emergency psychology to an extension of the biomedical model, focused on the diagnosis and prevention of psychopathology, raises questions about the specificity and distinctive contribution of the discipline. The review underscores the need for a paradigm shift in emergency psychology toward more holistic, integrated, and community-centered approaches, emphasizing the importance of developing interventions that address both individual and collective resilience in crisis situations. The study’s scope was limited by its focus on English-language articles from the past decade and the use of specific keywords, potentially overlooking relevant interventions and alternative perspectives that could have emerged from a broader, multilingual search strategy. In terms of future research, this perspective suggests the need to develop methodologies and intervention protocols that go beyond clinical diagnosis and foster governance of interactions in emergency contexts, promoting effective and shared crisis management.